2009
DOI: 10.1088/0022-3727/42/19/195304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal treatment on the band offsets and interfacial properties of HfOxNygate dielectrics

et al.

Abstract: Band offsets and interfacial properties of HfOxNy films grown on Si(1 0 0) through radio-frequency reactive magnetron sputtering were investigated by x-ray photoelectron spectroscopy. The changes in the conduction band offset, the valence band offset, as well as in the interfacial properties were obtained as a function of the annealing temperature. The interfacial layer is unavoidably formed for the deposited films and the composition of the interfacial layer is most likely Hf-silicate and SiOx. With the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Among remaining oxides, Al 2 O 3 , Y 2 O 3 , ZrO 2 , and HfO 2 have been selected for research study for the past few years. Metal silicate, such as Hf, Zr, and Y has also attracted extensive attention due to their thermodynamic stability with Si [31][32][33][34][35].…”
Section: Selection and Consideration In High-k Dielectrics Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among remaining oxides, Al 2 O 3 , Y 2 O 3 , ZrO 2 , and HfO 2 have been selected for research study for the past few years. Metal silicate, such as Hf, Zr, and Y has also attracted extensive attention due to their thermodynamic stability with Si [31][32][33][34][35].…”
Section: Selection and Consideration In High-k Dielectrics Candidatesmentioning
confidence: 99%
“…Since accurate determination of the optical constant is an essential prerequisite for device simulations and gives the opportunity to improve material preparation, this necessitates the investigation of optical characteristics for Hf-based high-k gate dielectrics in the wide energy range. By spectroscopy ellipsometry (SE) data analysis on the basis of the accurately parameterized Taul-Lorentz model, the optical constants and the complex pseudo dielectric functions of HfO x N y films with nitrogen-incorporation content have been studied systematically [15,33,35,90]. Fig.…”
Section: Hf-based Oxides Gate Dielectricsmentioning
confidence: 99%
“…The degradation of electrical characteristics can be induced by incorporating nitrogen at the interface between dielectric thin films and the Si substrate [14,15]. Generally, there are several nitridation methods including chemical vapor deposition (CVD) [16], re-oxidation of HfN films formed by physical vapor deposition (PVD) [17], and thermal annealing with NH 3 [18] for HfO x N y thin films that have a high dielectric constant and thermal stability [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al deposited HfO x N y samples on Si(100) by using radio-frequency reactive magnetron sputtering and have demonstrated that valence band offset and conduction band offset of the HfO x N y increases with annealing temperature. Table V summarizes the effect of annealing temperature on the band offsets of HfO x N y films [80]. [82].…”
Section: N-dopingmentioning
confidence: 99%